Nilai Kearifan Lokal Pappaseng To Riolo Bugis dalam Buku Kearifan Budaya Lokal Karya Kaimuddin Mabbaco (Kajian Hermeneutika Paul Ricoeur) - Marwah Sari M.; Nensilianti Nensilianti; Andi Agussalim AJ (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract: This study aims to describe the value of local wisdom pappaseng to riolo Bugis in the book Local Cultural Wisdom by Kaimuddin Mabbaco using three stages, namely, understanding symbols, giving symbol meanings, and thinking symbols. This research is qualitative, the source of this research data is in the form of text from pappaseng to riolo Bugis from the book Local Cultural Wisdom by Kaimuddin Mabaco. The abbreviation used in this pnelitian is Paul Ricoeur's Hermeneutics, the results of the study show the existence of meaning interpretation using the 3 stages of Paul Ricoeur's Hermeneutics method, namely the understanding of symbols, the giving of symbol meanings, and symbol thinking each interpretation is an attempt to dismantle the veiled meanings in the value of pappaseng wisdom is the result of the meaning of the pappaseng text to find out what local wisdom values are contained in the pappaseng to riolo Bugis text in the book of local cultural wisdom by Kaimuddin Mabbaco Keywords: Hermeneutics, the value of local wisdom, pappaseng.